A novel M2Ga2GeO7:N3+ (M = Ca, Ba, Sr; N = Cr, Nd, Er) sub-micron phosphor with multiband NIR emissions: preparation, structure, properties, and LEDs. (6th July 2021) - Li, Zhihua; Ding, Xin; Yu, Bing; Min, Yu; He, Bin; Shen, Youqing; Cong, Hailin
Abstract: Near-infrared (NIR) emission materials can be widely applied in various fields, such as food detection, imaging, treatment, electronic products. With the trend of miniaturization of equipment, smaller materials are needed. In this work, we successfully synthesized a series of M2 Ga2 GeO7 :N 3+ (M = Ca, Ba, Sr; N = Cr, Nd, Er) samples and then focused on the study of Nd 3+ doped Sr2 Ga2 GeO7 (SGGO). A series of SGGO: x Nd 3+ sub-micron phosphors were prepared via a microwave-assisted sol–gel process combined with subsequent calcination at 750 ℃, and the structural information and luminescent properties were systematically studied. SGGO is a representative tetragonal crystal and belonging to the space group of P 4 ̄ 21m (113). The Nd 3+ ions occupy eight-coordinated Sr 2+ sites in the crystal lattice. From SEM analysis, the average particle size distribution is 219.7 ± 41.4 nm. The sub-micron phosphors have rich excitation spectra ranging from 350 nm to 850 nm and can produce multiband NIR emissions of 1331, 1056, and 905 nm when excited by ultraviolet and NIR light. The maximum emission intensity was obtained by optimizing the doping ratio of Nd 3+ ions. A commercial chip was then utilized to fabricate light-emitting diodes (LEDs) to verify its application potential in NIR-II mini-LEDs. Compared with blue light LEDs, the as-prepared LEDs had good imaging penetration depth and could be clearly observed under 10 mm of chicken breast coverage. The maximum imaging penetration depth can be 33 mm.